2009
DOI: 10.1007/s10096-009-0729-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for community-acquired acute gastroenteritis in north-west Germany in 2004

Abstract: In developed countries, acute gastroenteritis (AGE) is a major source of morbidity. However, only a few studies have estimated its incidence and the associated medical burden. This population-based study determined the incidence of community-acquired AGE patients seeking medical care and the relative role of various pathogens. Stool samples from patients with AGE presenting to a general practitioner (GP), pediatrician, or specialist in internal medicine for that reason were screened for various bacterial and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
88
4
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 36 publications
(35 reference statements)
13
88
4
7
Order By: Relevance
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussioncontrasting
confidence: 55%
“…Further work is needed to validate the use of a cycle threshold value cutoff for use in studies without a control group. Asymptomatic norovirus infection is very common (1,16,21,(33)(34)(35). Therefore, this quantitative approach provides the most rigorous estimate of norovirus disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Types 40 and 41 are responsible for 1%-20% cases of diarrhoea in young children. Other species such as A (types 12, 18, and 31), C (types 1, 2, and 5) and D (types 28,29,30,32,37,[43][44][45][46] have also been associated with diarrhoea (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Norovirus infection has also been identified in a substantial proportion of individuals with no IID symptoms in several community-based studies, with prevelances of up to 16 % reported in high-income countries [1,[5][6][7]. Volunteer studies have demonstrated the occurrence of norovirus infection with no concurrent IID symptoms after experimental inoculation [8,9].…”
Section: Introductionmentioning
confidence: 99%